2020
DOI: 10.1145/3415226
|View full text |Cite
|
Sign up to set email alerts
|

Social Norm Vulnerability and its Consequences for Privacy and Safety in an Online Community

Abstract: Within online communities, social norms that both set expectations for and regulate behavior can be vital to the overall welfare of the community--particularly in the context of the privacy and safety of its members. For communities where the cost of regulatory failure can be high, it is important to understand both the conditions under which norms might be effective, and when they might fail. As a case study, we consider transformative fandom, a creative community dedicated to reimagining existing media in of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Fiesler and Proferes (2018) found that Twitter users are largely unaware that researchers are permitted to use public data without explicit consent and believe that researchers should not be able to use tweets without prior permission. However, prior work has also found that users’ attitudes about research use of social media data depend on contextual factors, such as how the research is conducted and the topic of the study (Fiesler & Proferes, 2018), the size of the community (Hudson & Bruckman, 2004), and who is using the data (Dym & Fiesler, 2020; Fiesler & Proferes, 2018; Gruzd & Mai, 2020). Qualitative research by Beninger (2017) explored users’ feelings about social media research, finding diverse responses across participants including skepticism about research using social media data; acceptance, particularly among those who viewed social media data as already public; and ambivalence among those who felt there was nothing that could be done to prevent being studied.…”
Section: Introductionmentioning
confidence: 99%
“…Fiesler and Proferes (2018) found that Twitter users are largely unaware that researchers are permitted to use public data without explicit consent and believe that researchers should not be able to use tweets without prior permission. However, prior work has also found that users’ attitudes about research use of social media data depend on contextual factors, such as how the research is conducted and the topic of the study (Fiesler & Proferes, 2018), the size of the community (Hudson & Bruckman, 2004), and who is using the data (Dym & Fiesler, 2020; Fiesler & Proferes, 2018; Gruzd & Mai, 2020). Qualitative research by Beninger (2017) explored users’ feelings about social media research, finding diverse responses across participants including skepticism about research using social media data; acceptance, particularly among those who viewed social media data as already public; and ambivalence among those who felt there was nothing that could be done to prevent being studied.…”
Section: Introductionmentioning
confidence: 99%
“…In reporting our results, we note that prior work regarding research ethics for Twitter has shown some users may be uncomfortable with their content being amplified beyond the platform, particularly when the content is on a sensitive topic or the user is in a vulnerable position [21,23]. In weighing potential harms against the utility of direct quotes for this part of our analysis, we decided in reporting our results to employ ethical fabrication [55] and paraphrase tweets so that the substance is the same but that they are not discoverable through a search [15].…”
Section: Methodsmentioning
confidence: 93%
“…For example, LGBTQ+ people use fan communities to explore their identity safely, away from harms they might experience for exploring that identity elsewhere, and to connect with LGBTQ+ communities and resources they cannot access anywhere else [18]. As a result, fan communities also have strong social norms around privacy and secrecy to keep those vulnerable community members safe [11,20].…”
Section: Pillowfort and Participatory Culturementioning
confidence: 99%